Kelangsungan Hidup dan Kesehatan Ikan Nila (Oreochrromis niloticus) pada Transportasi Sistem Tertutup Dengan Bahan Anastesi Ekstrak Akar Tuba - Tanbisyakur, Tanbisyaskur; Achadi, Teguh; Prasasty, Gita Dwi (Jurnal Perikanan dan Kelautan, 2018)
This study aims to determine the effect of adding Tuba Root extract to the media in increasing the survival of tilapia seeds in closed system transportation.The study was conducted in July - October 2018 at the Laboratory of Aquaculture, Aquaculture Study Program, Faculty of Agriculture, Universitas Sriwijaya. The research method used a completely randomized design with four treatments and three replications. Tilapia seed transport media treated with PO: Without the addition of tuba root extract, P1: Tuba root addition with a concentration of 0,00025 ml / l, P2: Addition of tubal root extract concentration 0,00050 ml / l, P3: Addition of tubal root extracts concentration 0.0010 ml / l.The results showed that after the fish was transported for 5 hours, the treatment of the addition of tuba root extract with a concentration of 0.00025 ml / l can reduce the rate of fish metabolism and provide the best results for survival, about 98.3%,erythrocyte 2.6 x 106 cell / mm3, Hemoglobin 7.7 g /dl, Hematocrit 22% and operculum opening 108.67 times / minute.Based on the analysis of variance, the application of tuba root extract on transportation media with a concentration of 0.00025 ml / l has a significant and better effect than other treatments. The results also showed that the addition of tuba root extract above the concentration of 0.00025 ml / l could cause fish to experience death in tilapia seeds in closed system transportation.